The effectiveness of problem based learning with authentic assessment towards students’ mathematical problem solving ability at 11th grade of Tran Nhan Tong Senior High School in Ho Chi Minh City, Vietnam - Mawarti, Sela; Masrukan, Masrukan; Asikin, Mohammad (Department of Mathematics, Universitas Negeri Semarang, 2018)
The purpose of this research was to find out whether Problem Based Learning (PBL) learning with authentic assessment affects the students' mathematical problem solving ability. The method of this research was quantitative research method. Its population was 11th grade of Tran Nhan Tong Senior High School Ho Chi Minh City, Vietnam in academic year 2017/2018. By using the cluster random sampling, class 11A1 was selected as a control class that gained conventional learning in Vietnam, class 11A2 as an experiment class 1 that obtained PBL learning with authentic assessment, and class 11A3 as experiment 2 class that obtained PBL learning. The data collection techniques were documentation and test method. The result of the research showed that the result of mathematical problem solving test at the experiment class 1 successfully reached classical completeness more than or equal to 75% of the students in the class, and students’ mathematical problem solving ability at the experiment class 1 was better than at the experiment class 2, while students’ mathematical problem solving ability at the experiment class 2 was better than at the control class.